Anodized Iron Oxide Nanostructures on Different Carbon Steels for Photoelectrochemical Water Splitting. Issue 7 (15th June 2016) - Deng, Hongda
Abstract: In this study, two different nanostructural iron oxide films were prepared on two kinds of carbon steels (CS) with different contents of impurities via anodization in a mixture of aqueous ammonium fluoride solution and ethylene glycol, respectively, and apply to photoelectrochemical (PEC) water splitting. After annealing, iron oxide nanotubes (NTs) was coated on surface of lower purity CS and iron oxide nanoporous (NPs) was coated on surface of higher purity CS via scanning electron microscope. X‐ray diffraction pattern shows both of samples contain a major phase of α‐Fe2 O3 and a slight phase of Fe3 O4 . Compared with NPs, NTs behaves better absorbance ability in visible spectra range via UV‐visible absorbance spectra. From PEC response, the iron oxide NTs showed higher water splitting performance (0.10 mA/cm 2 at 0.4 V vs. Ag/AgCl) than NPs (0.04 mA/cm 2 at 0.4 V vs. Ag/AgCl) due to better absorbance, higher car‐ rier concentration and low charge transfer resistance. Abstract : Two different iron oxide nanostructures were prepared on two kinds of carbon steels (CS) via anodization, respectively. Iron oxide nanotubes (NTs) were coated on lower purity CS and iron oxide nanoporous (NPs) was coated on higher purity CS. From PEC response, NTs showed higher performance than NPs due to better absorbance, higher carrier concentration and low charge transfer resistance.